Aplikasi dan Tinjauan Kinetika Hasil Fraksinasi Produk Pirolisis Cangkang Biji Jambu Mete Uji sebagai Antijamur Candida albicans - Ustamuni Ustamuni; Laily Nurliana; Rustam Musta (Indonesian Journal of Chemical Analysis (IJCA), 2019)
Research on application and kinetics study of fractionation pyrolysis product from cashew nut shell as antifungal of Candida albicans has been carried out. This study aims to determine the constituent compounds, antifungal activity and chemical kinetics including order and rate constants antifungal activity C. albicans from fractional distillation results of cashew nut shell pyrolysis products. Cashew nuts were hydrolyzed and purified using a fractional distillation device. The results of the antifungal activity test C. albicans from fractional distillation results of cashew nut shell pyrolysis products showed that the inhibitory power varied from each concentration variation of 12.5%, 25%, 50%, 75%, and 100%. The concentration of 100% was the highest inhibitory characterized by the formation of a clear zone of 18.23 mm which indicates that the inhibitory force is a strong category. The clear zone that has been formed was calculated in terms of its chemical kinetics including the reaction order and the activity rate constant. The reaction order of antifungals C. albicans from the results of fractional distillation of cashew nut shell pyrolysis products is 0.15 with a constant activity rate of 8.74.